Innovative Approaches in Aquaculture Research (VOLUME-1) - Minare, Anubhuti; Vyas, Vipin; Garg, Rajkumar; Kaur, Pinky (AG Volumes, 2025)
This book is a comprehensive compilation of recent research and field-based studies in the domain of freshwater aquaculture and fish reproductive biology, with special emphasis on innovative breeding techniques, sustainable fish farming models, and conservation of indigenous fish biodiversity. It brings together a series of practical investigations and scientific analyses conducted in the central Indian region, particularly around Bhopal, Madhya Pradesh.The chapters in this volume cover key aspects such as:• Induced breeding of commercially and nutritionally important fishes including ornamental species like Oranda Goldfish, and indigenous species like Clarias batrachus and Heteropneustes fossilis using hormonal agents such as Ovafish, Ovatide, and Gonopro-FH.• Practical demonstrations of mini portable hatchery systems, offering scalable and low-cost solutions for rural fish seed production.• Polyculture systems integrating Small Indigenous Fish Species (SIFS) with Indian Major Carps, aimed at enhancing pond productivity and promoting dietary diversity in rural households.• Experimental studies on the effect of environmental manipulations like greenlight exposure on the growth of Indian Major Carps, introducing low-cost innovations for increasing yield.• Morphological and reproductive studies of small indigenous fishes and catfish species, essential for understanding reproductive cycles, gonadal maturation, and species conservation.• Wetland and riverine ecosystem assessments around Bhopal, documenting current biodiversity status, ecological threats, and conservation priorities.The book is designed to serve a wide readership including fisheries students, hatchery technicians, extension officers, policy planners, and small-scale farmers. It not only contributes to the academic understanding of fish breeding and ecosystem dynamics but also provides practical insights into field-level technologies and strategies for sustainable aquaculture and biodiversity conservation.By linking laboratory research to on-ground implementation, this book represents a significant step toward technology transfer and livelihood enhancement in the fisheries sector, especially for the rural communities engaged in aquaculture.